Extracardiac coronary steal induced by upper limb hyperemia: a feature of internal mammary artery arteriogenesis. (14th October 2021) - Bigler, M R; Buffle, E; Stoller, M; Grossenbacher, R; Tschannen, C; Seiler, C
Abstract: Introduction: Function of naturally existing internal mammary artery (IMA)-to-coronary artery anastomoses has been shown by augmented blood supply to the coronary collateral circulation in response to IMA occlusion. Theoretically, this functional connection is invertible and can cause coronary steal, the verification of whose hypothesis would provide alternate proof to the mentioned functional evidence. Method: This was a prospective observational study including 40 patients with chronic coronary syndrome and IMA occlusion, and 40 propensity score matched controls (placebo group) without IMA occlusion. Primary study endpoint was the inter-group difference in coronary collateral function (i.e., collateral flow index, CFI) as obtained at 30, 45 and 60 seconds following a proximal coronary artery balloon occlusion. CFI is the ratio between simultaneous mean coronary occlusive pressure divided by mean aortic pressure both subtracted by central venous pressure. To provoke a steal phenomenon, upper limb hyperemia was induced by upper arm blood pressure cuff deflation following a 5-minute supra-systolic inflation ipsilateral to the sensor-wired coronary artery with release immediately after the first CFI measurement. Results: Between the first and the second CFI-measurement, CFI change (i.e., CFI@45s minus CFI@30s) was absent in the verum group while there was CFI recruitment in the placebo group: 0.000±0.023 and +0.009±0.013, respectively; p=0.032. Conclusion: Among patients with artificial IMA occlusion, induction of ipsilateral upper limb hyperemia provokes extracardiac coronary steal as expressed by temporarily absent collateral recruitment as it normally takes place without upper limb hyperemia. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Swiss National Sciences Foundation